Spontaneous Synthesis of [FeII(Atrz)3]SO4 and its Analogues Through Accelerated Ageing: New Insights from Small‐Scale Reactions. Issue 64 (19th September 2022) - Lonergan, Rhona F.; Conway, Georgina A.; Doheny, Patrick W.; Shepherd, Helena J.
Abstract: Accelerated ageing reactions that take place between two solid materials on contact in the absence of added solvent have been used to synthesize two spin‐crossover‐active 1D coordination polymers and one of their Cu(II) analogues. The hygroscopy of the ligands and the relative humidity of the reaction chamber have been shown to be particularly important factors in the rate of reaction. Small‐scale reactions between a few individual crystals have allowed observation of deliquescence of the 4‐aminotriazole ligand at high humidity. The metal salt does not dissolve, and the ligand diffuses into the crystal of the metal salt during the reaction. In the case of the Cu analogue, the formation of the product causes the crystal of the metal salt to deform with the formation of pseudocrystals, which have a fibrous structure. Abstract : Accelerated ageing can be used to synthesize functional materials including spin crossover systems. Reactions proceed between a metal salt and a ligand placed in contact in a humid environment without any solvent or applied energy. Optical microscopy of small‐scale reactions can be used to derive mechanistic information about accelerated ageing.